Study guides

☆☆

Q: What is -10x -6 equals -12?

Write your answer...

Submit

Still have questions?

Related questions

6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1

-12-6x=12-10x we can add 12 to both sides, getting: -6x=24-10x then we can add 10x to both sides: 4x=24 divide both sides by 4: x=6 the answer is x equals 6.

10x-7=4x+5 +7 +7 10x=4x+12 -4x -4x 6x=12 /6 /6 x=2

If: y = 10x -12 and y = x^2 +20x +12 Then: x^2 +20x +12 = 10x -12 Transposing terms: x^2 +10x +24 = 0 Factorizing: (x+6)(x+4) = 0 => x = -6 or x = -4 Points of intersection by substitution are at: (-6, -72) and (-4, -52)

2x2 = 10x + 12 2x2 - 10x - 12 = 0 x2 -5x -6 = 0 x2 - 6x + x - 6 = 0 x(x -6) + 1(x -6) = 0 (x+1)(x-6) = 0 x = -1 or x = 6

10x + 6 = 12x - 18 Subtract 10x from both sides: 6 = 2x - 18 Add 18 to both sides: 24 = 2x Divide both sides by 2: 12 = x Therefore, x = 12

6x - 3x = 5x - 10x + 12 6x - 3x - 5x + 10x = 12 8x = 12 8x/8 = 12/8 x = 12/8 = 3/2 x = 1.5

5=4x 1.25=x

10x + 3 = 15 10x = 15 - 3 10x = 12 x = 1.2

-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1

x + 13x + 10x = 50 - 6

-2(5x+3)-2x<-3(2x-4)+2

People also asked